Meningkatkan Pemahaman Konsep Peserta Didik Pada Materi Ikatan Kimia Dengan Metode Pembelajaran Example Non Example Menggunakan Animasi Di Kelas X MIPA 1 SMANegeri 6 Kerinci - Husni Husni (Universitas Batanghari Jambi, 2022)
Chemical Bond material was one of abstract concept that made a Chemistry Teacher should always correct and innovates his or her learning method. The researcher found out that the low students’ achievement on chemical bond material at grade X MIPA 1 SMAN 6 Kerinci was caused by the implementation of conventional method towards conceptual comprehension. Animated example non example learning was one of scientific method which was regarded appropriate to be used in teaching chemical bond lesson. This research aimed at figuring out whether or not the implementation of Example non Example learning method using animation could improve the students’ conceptual comprehension and the cognitive achievement at grade X MIPA1 SMAN 6 Kerinci Academic year 2021/2022. The research participants were the students at grade X MIPA 1 SMAN 6 Kerinci, first semester in academic year 2021/2022. The result of the research showed that the students’ cognitive achievement at grade X MIPA 1 SMAN 6 Kerinci who were taught by using animated example no example learning method improved significantly. It could be seen that theaverage score75,18 And the average score was 81,96. In conclusion, the implementation of animated example non example improved the students’ cognitive achievement at grade X MIPA 1 SMAN 6 Kerinci significantly.